Optimising dopants and properties in BiMeO3 (Me = Al, Ga, Sc, Y, Mg2/3Nb1/3, Zn2/3Nb1/3, Zn1/2Ti1/2) lead-free BaTiO3-BiFeO3 based ceramics for actuator applications. Issue 12 (September 2018) - Murakami, Shunsuke; Ahmed, Nihal Thafeem Ahmed Faheem; Wang, Dawei; Feteira, Antonio; Sinclair, Derek C.; Reaney, Ian M.
Abstract: A crystallochemical framework is proposed based on electronegativity difference ( e n ) and tolerance factor ( t ) to optimise the BiMeO3 dopants and therefore the piezoelectric and high-field strain response in BaTiO3 -BiFeO3 based ceramics. Compositions in the series 0.05Bi( Me )O3 -0.25BaTiO3 -0.7BiFeO3 (B Me -BT-BF, Me : Y, Sc1/2 Y1/2, Mg2/3 Nb1/3, Sc, Zn2/3 Nb1/3, Zn1/2 Ti1/2, Ga, and Al) were fabricated using solid state synthesis and furnace cooled. Scanning electron microscopy and X-ray diffraction revealed that only Bi(Mg2/3 Nb1/3 )O3 and BiScO3 dopants, which lie in a narrow range of e n vs. t, form homogeneous ceramics, free from secondary phases reflected in their superior piezoelectric coefficients ( d 33 ∼145 pC/N). All other BiMeO3 additions exhibited either secondary phases (Y) and/or promoted a two-phase perovskite matrix (Zn, Ga and Al). The promising initial properties of BiScO3 doped compositions prompted further studies on 0.05BiScO3 -(0.95- x )BaTiO3 -( x )BiFeO3 (BS-BT-BF, x = 0.55, 0.60, 0.625, 0.65, and 0.70) ceramics. As x increased the structure changed from predominantly pseudocubic to rhombohedral, resulting in a transition from a relaxor-like to ferroelectric response. The largest d 33 * (465 pm/V) was achieved for x = 0.625 under 5 kV/mm at the crossover from relaxor to ferroelectric behaviour. BS-BT-BF with x = 0.625 showed >0.3% strain under 6 kV/mm up to 175 °C, demonstrating its potential for actuator applications.